Agricultural mechanization: field of action for the agronomy - Pérez de Corcho Fuentes, Jorge Simón (2017)
From the analysis of several sources and the legal regulations in force, this paper addresses the situation of the Agricultural Mechanization as a professional field of action within the Agricultural Engineering, its characteristics and requirements in Ecuadorian conditions. The resulting analysis -written from a detailed literature review and discussion with experts within the field-, will be useful for the understanding of the role that the professionals within the field play in the management and administration of agricultural machinery, as well as in the learning process. Finally, it is concluded that the agricultural machinery management is an important field of action for the Agricultural Engineer, so that it demands training for the selection and planning, as well as in the estimation of costs and yields.